Flooding risks and housing markets: a spatial hedonic analysis for La Plata City - Rabassa, Mariano Javier (2016)
Fil: Rabassa, Mariano Javier. Pontificia Universidad Católica Argentina. Facultad de Ciencias Económicas; Argentina